The Impact of Cereal Grain Composition on the Health and Disease Outcomes - Garutti, Mattia; Nevola, Gerardo; Mazzeo, Roberta; Cucciniello, Linda; Totaro, Fabiana; Bertuzzi, Carlos A.; Caccialanza, Riccardo; Pedrazzoli, Paolo; Puglisi, Fabio (Frontiers in Nutrition, 2022)
Whole grains are a pivotal food category for the human diet and represent an invaluable source of carbohydrates, proteins, fibers, phytocompunds, minerals, and vitamins. Many studies have shown that the consumption of whole grains is linked to a reduced risk of cancer, cardiovascular diseases, and type 2 diabetes and other chronic diseases. However, several of their positive health effects seem to disappear when grains are consumed in the refined form. Herein we review the available literature on whole grains with a focus on molecular composition and health benefits on many chronic diseases with the aim to offer an updated and pragmatic reference for physicians and nutrition professionals.